2016
DOI: 10.1017/s0024282916000499
|View full text |Cite
|
Sign up to set email alerts
|

Five new species and one new record ofAstrothelium(Trypetheliaceae, Ascomycota) from Thailand

Abstract: Five new species and one new record of Astrothelium (Trypetheliaceae) are reported from Thailand. Phylogenetic analysis of four DNA loci (ITS, nuLSU, mtSSU rDNA and RPB1) demonstrated the placement of the new species within Astrothelium, as well as their distinction from similar or related taxa. The new species are: A. flavocoronatum, with a yellow pigment surrounding the ostiole, and 3-septate ascospores 22-28 × 8·0-9·5 µm; A. macrostiolatum, with large whitish ostiolar area, a hamathecium inspersed with smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…PCR was performed using a thermal cycler Life ECO (Hangzhou Bioer Technology Co., China) as follows: initial denaturation for 1 min at 94 °C and 38 cycles of 94 °C for 1 min, 52 °C for 45 s (LR0R/LR3) and 53 °C for 45 s (mrSSU1/ MSU7), followed by an extension at 72 °C for 1 min and a final extension at 72 °C for 5 min. DNA purification and sequencing methods followed Luangsuphabool et al (2016).…”
Section: Molecular Datamentioning
confidence: 99%
“…PCR was performed using a thermal cycler Life ECO (Hangzhou Bioer Technology Co., China) as follows: initial denaturation for 1 min at 94 °C and 38 cycles of 94 °C for 1 min, 52 °C for 45 s (LR0R/LR3) and 53 °C for 45 s (mrSSU1/ MSU7), followed by an extension at 72 °C for 1 min and a final extension at 72 °C for 5 min. DNA purification and sequencing methods followed Luangsuphabool et al (2016).…”
Section: Molecular Datamentioning
confidence: 99%
“…Recent studies on the diversity of lichen-forming fungi in Thailand have dramatically increased our knowledge of these organisms in Southeast Asia, with numerous new records and new species discovered in a number of different habitats, including coastal forests (Aptroot et al 2007;Kalb et al 2012Kalb et al , 2016aKalb et al , 2016bKantvilas et al 2010;Luangsuphabool et al 2016aLuangsuphabool et al , 2016bNaksuwankul et al 2016;Neuwirth et al 2014Neuwirth et al , 2016Papong and Lumbsch 2011;Papong et al 2014;Pitakpong et al 2015;Rangsiruji et al 2016;Sutjaritturakan and Kalb 2015;Buaruang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For the general section, a selection of morphological and anatomical images was provided by Felix Schumm and for the taxonomic section we also included images of five new species of Astrothelium described elsewhere in this issue (Luangsuphabool et al . 2016), provided by Ek Sangvichien.…”
Section: Methodsmentioning
confidence: 99%
“…An initial study by Del Prado et al (2006) demonstrated the placement of Trypetheliaceae within Dothideomycetes, and phylogeny of the family was refined through subsequent work by Nelsen et al (2009Nelsen et al ( , 2011Nelsen et al ( , 2014 and Lücking et al (2016a), showing that lichenized species of Arthopyrenia and Mycomicrothelia also belong here, and laying the groundwork for a much revised genus and species concept (Aptroot et al 2013a;Hyde et al 2013;Nelsen et al 2014;Luangsuphabool et al 2016;Lücking et al 2016a). This also stimulated further inventory work in several parts of the tropics, with the discovery of many new taxa Aptroot et al 2013bAptroot et al , 2016aLima et al 2013;Córdova-Chávez et al 2014;Weerakoon & Aptroot 2014;Flakus et al 2016;Luangsuphabool et al 2016;Lücking et al 2016b). The order Trypetheliales was eventually established for the family (Aptroot et al 2008;Hyde et al 2013), and recently a second family, Polycoccaceae, including lichenicolous fungi, was included in this order (Ertz et al 2015).…”
Section: Introductionmentioning
confidence: 99%